Timeliness of financial reporting: an analysis of good corporate governance mechanisms - Siti Maskupah; Ela Widasari; Siti Mudawanah (Universitas Muhammadiyah Malang, 2026)
Purpose: This study aims to examine the influence of Good Corporate Governance (GCG) mechanisms on the timeliness of financial reporting in consumer goods manufacturing companies. Methodology/approach: The research adopts a quantitative method using secondary data from companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. Logistic regression is applied to test the hypotheses. Findings: The results indicate that independent commissioners and managerial ownership do not significantly affect reporting timeliness. In contrast, institutional ownership and audit committees have a positive influence on the timely submission of financial reports. Practical and Theoretical contribution/Originality: The novelty of this study lies in its specific focus on internal GCG mechanisms (independent commissioners, institutional ownership, managerial ownership, and audit committees) within consumer goods manufacturing companies, a sector less explored compared to banking and financial industries. The study also covers the COVID-19 pandemic and post-pandemic recovery period (2019–2022), offering new perspectives on governance and reporting compliance in times of crisis. Additionally, the application of logistic regression provides methodological strength in analyzing categorical dependent variables such as reporting timeliness. Research Limitation: The study is limited to internal GCG mechanisms, consumer goods manufacturing companies, and an observation period of four years (2019–2022).